WHAT EMERGING TECHNOLOGY CAN DO FOR LEARNING ENVIRONMENTS: THE CASE OF MOOCS - Karen Ferreira-Meyers (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2014)
Abstract: This paper seeks to address the position of emerging trends in higher education. It is the written version of a public lecture given at UNSRI in May 2014. It starts with an overview of emerging trends (flipped courses, Open Learning Initiative, MOOCs) as described by the Horizon Report 2013, a brief literature review, and then continues to propose a more detailed overview of both Flipped Courses and Massive Open Online Courses with the intention of opening up the debate on the use of these in a higher education environment. Key words: emerging technology, learning environments, flipped courses, MOOCs